Structure of a Cyclic Peptide as an Inhibitor of Mycobacterium tuberculosis Transcription: NMR and Molecular Dynamics Simulations - Filia Stephanie; Usman Sumo Friend Tambunan; Krzysztof Kuczera; Teruna J. Siahaan (MDPI AG, 2024)
Background and Objectives: A novel antitubercular cyclic peptide, Cyclo(1,6)-Ac-CLYHFC-NH2, was designed to bind at the rifampicin (RIF) binding site on the RNA polymerase (RNAP) of Mycobacterium tuberculosis (MTB). This peptide inhibits RNA elongation in the MTB transcription initiation assay in the nanomolar range, which can halt the MTB transcription initiation complex, similar to RIF. Therefore, determining the solution conformation of this peptide is useful in improving the peptide's binding affinity to the RNAP. Methods: Here, the solution structure of Cyclo(1,6)-Ac-CLYHFC-NH2 was determined by two-dimensional (2D) NMR experiments and NMR-restrained molecular dynamic (MD) simulations. Results: All protons of Cyclo(1,6)-Ac-CLYHFC-NH2 were assigned using TOCSY and NOE NMR spectroscopy. The NOE cross-peak intensities were used to calculate interproton distances within the peptide. The JNH-HCα coupling constants were used to determine the possible Phi angles within the peptide. The interproton distances and calculated Phi angles from NMR were used in NMR-restrained MD simulations. The NOE spectra showed NH-to-NH cross-peaks at Leu2-to-Tyr3 and Tyr3-to-His4, indicating a βI-turn formation at the Cys1-Leu2-Tyr3-His4 sequence. Conclusions: The NMR-restrained MD simulations showed several low-energy conformations that were congruent with the NMR data. Finally, the conformation of this peptide will be used to design derivatives that can better inhibit RNAP activity.